Identification of polyphenolic compounds in wolfberry juice - CAI Wenwen; ZHANG Gensheng; SHAN Yongkai; ZHANG Hongcheng; QIAO Jiangtao (Shipin yu jixie)
ObjectiveThis paper aims to promote the deep processing of wolfberry products.MethodsHigh-performance liquid chromatography-quadrupole time-of-flight tandem mass spectrometry (HPLC-QTOF-MS/MS) was used to qualitatively and quantitatively analyze polyphenolic compounds in wolfberry juice.ResultsA total of seven polyphenolic compounds were identified in red wolfberry juice, including five phenolamides and two flavonoids; Eight polyphenolic compounds were identified in black wolfberry juice, including three phenolamides and five flavonoids (four of which were anthocyanins). Quantitative analysis of the identified compounds showed that phenolamides accounted for over 80% of the polyphenolic compounds in red wolfberry juice, while flavonoids were the dominant compounds in black wolfberry juice.ConclusionRed wolfberry juice and black wolfberry juice have significant species differentiation in the composition and functional properties of polyphenolic compounds.